Denmark : Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses key findings of the Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision (BCPs) on Denmark. Denmark has a high level of compliance with the BCPs. The Danish Financial Supervisory Authority has appropriate legal authority to carry out supervision effectively, and its risk-based approach has focused well on the key elements of risk within its banking system. The compliance with the credit-risk related principles is uniformly high and the provisioning policies have been adequately enhanced. Its overall supervision is also considered sound, although resource constraints result in an extended supervision cycle and some risk areas receiving insufficient attention.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet